2022
DOI: 10.1523/jneurosci.0705-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Control of Forelimb Motor Adaptation

Abstract: The ability to perform skilled arm movements is central to everyday life, as limb impairments in common neurologic disorders such as stroke demonstrate. Skilled arm movements require adaptation of motor commands based on discrepancies between desired and actual movements, called sensory errors. Studies in humans show that this involves predictive and reactive movement adaptations to the errors, and also requires a general motivation to move. How these distinct aspects map onto defined neural signals remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Predictive control of movement is important, since feedback control can be too slow to produce fast smooth movements ( 1 , 9 , 10 ). Thus, we suggest that premovement HON signals contribute to movement planning, as well as adaptation ( 11 ). Since the purpose of premovement HON activity was unknown, this advances our understanding of the role of this core, evolutionarily conserved, neural module in adaptive behavior.…”
Section: Discussionmentioning
confidence: 96%
“…Predictive control of movement is important, since feedback control can be too slow to produce fast smooth movements ( 1 , 9 , 10 ). Thus, we suggest that premovement HON signals contribute to movement planning, as well as adaptation ( 11 ). Since the purpose of premovement HON activity was unknown, this advances our understanding of the role of this core, evolutionarily conserved, neural module in adaptive behavior.…”
Section: Discussionmentioning
confidence: 96%
“…There is some evidence that distinct areas of the hypothalamus may impact motor behavior. A previous study has demonstrated that hypothalamic orexin/hypocretin neurons localized in the lateral hypothalamus are involved in skilled movements and especially in error-based motor adaption [ 93 ]: After compromised or even lost motor task, the so-called “internal model”, understood as the entirety of cortical motor commands, uses the discrepancy between the desired and present movement trajectory to currently update motor command across attempts and thus reduces error [ 93 ]. In the present study, STN-HFS did not change glucose metabolism in the LH, however, resulted in a decrease of [ 18 F]FDG uptake in the VMH.…”
Section: Discussionmentioning
confidence: 99%
“…69,70 However, this HON activation did not seem to control the amount of food consumed, but instead facilitated movement patterns that ensured steady food supply over time. 69 Overall, since these studies suggest that HON activity promotes mobile behaviours that either increase or maintain the likelihood of food discovery or acquisition, we propose that HON activity can be viewed as a driver for appetitive behaviours. This is a distinct function from food intake, as discussed further below.…”
Section: Hypocretin/orexin Neurons As Drivers Of Mobile Behavioursmentioning
confidence: 96%
“…To answer this question, these movement patterns need to have a known goal. When complex, non‐locomotor movements (skilled pulling on a robotic handle using one forelimb) motivated by a food goal were recently examined, it was found that they were also associated with HON activation 69,70 . However, this HON activation did not seem to control the amount of food consumed, but instead facilitated movement patterns that ensured steady food supply over time 69 .…”
Section: Hypocretin/orexin Neurons As Drivers Of Mobile Behavioursmentioning
confidence: 99%
See 1 more Smart Citation